The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1111/j.1365-3059.2008.01840.x
|View full text |Cite
|
Sign up to set email alerts
|

Quambalaria species associated with plantation and native eucalypts in Australia

Abstract: This study aimed to determine which species of Quambalaria are associated with shoot blight symptoms on Corymbia spp. An additional aim was to determine the presence and impact of quambalaria shoot blight on Eucalyptus species used in plantation development in subtropical and tropical regions of eastern Australia. Surveys identified three Quambalaria spp. -Q. pitereka , Q. eucalypti and Q. cyanescens -from native and plantation eucalypts, as well as amenity plantings, including the first confirmed report of Q.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(88 citation statements)
references
References 21 publications
(41 reference statements)
2
83
1
1
Order By: Relevance
“…Here it is also important to consider variation in the aggressiveness of strains and regional pathotypes to be used in artificial inoculations. Pegg et al (2008) have previously identified variability when studying a limited number of isolates of Q. pitereka from regions in Queensland and NSW. What is not known is the importance of pathogen variability in relation to aggressiveness and its role in disease development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here it is also important to consider variation in the aggressiveness of strains and regional pathotypes to be used in artificial inoculations. Pegg et al (2008) have previously identified variability when studying a limited number of isolates of Q. pitereka from regions in Queensland and NSW. What is not known is the importance of pathogen variability in relation to aggressiveness and its role in disease development.…”
Section: Discussionmentioning
confidence: 99%
“…In these plantations the pathogen infects foliage, stems and woody tissue of species of the genera Corymbia, Blakella and Angophora (Walker and Bertus 1971;Bertus and Walker 1974;Simpson 2000, Pegg et al 2008. Old (1990) described Q. pitereka as being endemic to the coastal forests of eastern Australia, where seedlings and young trees of Corymbia species can be severely affected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quambalaria cyanescens is a basidiomycetous plant pathogen, 29 which has undergone a number of taxonomic reassignments including, previously, Sporothrix cyanescens and Fugomyces cyanescens. 30,31 There are no human case reports of the isolation of Q. cyanescens from human specimens or as a cause of human pathology.…”
Section: -28mentioning
confidence: 99%
“…Treatment duration of at least 12 months is recommended for osteoarticular infections. 29 In conclusion, sporotrichosis needs to be considered as a differential diagnosis in patients from Australia's Northern Territory, alongside better known local endemic pathogens, which can cause sporotrichoid lesions (Nocardia spp.) or fixed cutaneous lesions non-responsive to conventional antibiotics (melioidosis, chromoblastomycosis, and cryptococcosis).…”
Section: -28mentioning
confidence: 99%